Some Options for Improving the Management of the IFS Cadre - Goyal, A. K. (Indian Forester, 2001)
The contribution of the Indian Forest Service in managing and conserving the forests and wildlife wealth of the country cannot be ignored. However, to increase the efficiency and effectiveness of the Service and to have a cadre of professionally competent and highly motivated officers, the management of the Service has to be improved both at the GoI as well as State Governments' level. Attempt has been made in this paper to list out some of the options for improving the management of the IFS cadre.